Improving Student Learning Participation in Social Studies Learning Through the Role Playing Method in Class VII of Junior High School (SMP) N 5 Padang - Dimas Sartika; Etmi Hardi; Indyana Indyana (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to improve learning participation through the role playing method in the subject of Social Studies class VII.8 at SMP Negeri 5 Padang. This type of research is classroom action research (CAR). The subjects of the study were 33 students of class VII.8 SMP Negeri 5 Padang. The object of this study is learning participation in the subject of Social Sciences through the application of the role playing method. Data collection techniques used observation sheets, questionnaires, field notes and documentation. The data from the study were analyzed descriptively qualitatively. The results of this study indicate that the application of the role playing method in Social Studies learning can improve learning participation. For the aspect of learning participation in cycle I, participation in asking questions had a percentage of 53.57%, answering questions 52.38%, completing assignments 54.76%, discussing 52.38%, taking notes on lesson materials 55.95%, working on questions 53.57%, completing tests individually 53.57%, and concluding lesson materials 51.19%. In the action stage of cycle II, the percentage of each aspect increased from the results of the score obtained in cycle I, participation in asking questions had a percentage of 76.19%, answering questions 79.76%, completing assignments 82.14%, discussing 80.95%, taking notes on lesson materials 77.38%, working on questions 78.57%, completing tests individually 77.38%, and concluding lesson materials 77.38%.